The Replacement Killers - Antoine, Fuqua; Trejo, Danny, 1944-; Jürgen Prochnow; Kenneth Tsang; Michael Rooker; Mira Sorvino; Til Schweiger; YunFat Chow (USA Brillstein-Grey Entertainment, 1998)
John Lee is the best hitman money can buy. But when John refuses to kill because of the seven year-old son of his target, John's bosses send someone after John to kill him and then take his place in the ring of hitmen. John then teams up with Meg Coburn to help him escape these ""Replacement Killers.""
Failing to kill because of his conscience, a troubled hitman gets aid from a forger to help him get papers to China. However, the drug-lord has hired replacements to finished the job and kill the hitman.
Ken Sanzel
Language(s): English
Subtitle(s): English, Polish, Czech, Hungarian, Hindi, Hebrew, Turkish, Greek
Keywords: Crime; Thriller; Action